Clinical features and lifestyle of patients with amyotrophic lateral sclerosis in Campania: brief overview of an Italian database - Francesca Trojsi; Anna Sagnelli; Nicola Vanacore; Giovanni Piccirillo; Luca Daniele; Francesco Izzo; Anna Laiola; Alfonso Di Costanzo; Giovanni Savettieri; Maria Rosaria Monsurrò; Gioacchino Tedeschi (Istituto Superiore di Sanità, 2012)
BACKGROUND: Physical activity and occupational exposures appeared to play a relevant role in pathogenesis of amyotrophic lateral sclerosis (ALS), a neurodegenerative disease of unknown origin. MATERIALS AND METHODS: We aimed to make an overview of the clinical characteristics and lifestyle (occupation and sport) of a population of 395 patients with ALS from Campania, in southern Italy. RESULTS: ALS onset resulted anticipated of about 11 years in industry workers, whilst the more frequent site of onset among farmers was upper limbs. Compared to non-athletes, athletes, particularly soccer players, showed a 7 years anticipation of ALS onset, with higher mortality after 5 years. DISCUSSION AND CONCLUSIONS: We suggest that subjects genetically prone to abnormal response to hypoxia during strenuous physical activity or exposed to neurotoxic agents, such as athletes, farmers or industry workers, might present increased risk to develop ALS. Future case-control and follow-up studies on our population should be implemented to deepen the present results.